A Low-Cost Instrument Based on Thick Film Sensors for Measuring Water Conductivity and Temperature - Wiranto, Goib; Dewa Putu Hermida, I.; A. Prabowo, Briliant; V. Manurung, Roberth; Widodo, Slamet; P. Aji, Gilang; Rahajoeningroem, Tri (International Journal of Engineering and Technology, 2018)
This paper describes the development of a portable instrument for measuring the conductivity and temperature of water. The system consisted of thick film sensors fabricated on alumina substrates using screen printing technique, and Arduino microcontroller to process and display the measured water parameters. The conductivity sensor was designed in a four-electrode configuration using AgPd conductor with a cell constant of 0.2 cm-1, whereas the temperature sensor was screen printed using RuO2 paste. The system has been tested to measure the conductivity of various water samples, including river and drinking water, and comparison with a commercial system demonstrated an error of less than 2.4 %. The maximum conductivity value that could be measured was under 2000 mS/cm, which makes the system suitable for monitoring of general drinking water and domestically polluted river water.Â